Decoding occupational well-being of teachers: does psychological capital and coping mechanism impact perceived stress? - Shilpa Badrinath Bidi; Vrinda Bhat; Sachin R. Chandra; Venisha Jenifer Dmello; Edwin Weesie; Mathew Thomas Gil; Simmy Kurian; Ambigai Rajendran (Cogent Psychology)
Teaching is a high-demand profession where teachers encounter work-related and distinct emotional turmoil of differing intensities while instructing and interacting with students. Teachers’ occupational wellness is compromised because of these experiences, which frequently lead to high levels of stress that exacerbate burnout. This empirical study is novel in addressing the positive psychology mediating and moderating effect between perceived stress and occupational well-being among teachers. Adopting a quantitative research design, a sample of 388 teachers was drawn and analyzed using Smart PLS 4. The findings uncovered that teachers experience multifarious challenges and stressors that negatively impact their occupational well-being. Further, psychological capital partially mediated the relationship; however, coping strategy did not mediate between perceived stress and occupational well-being. Coping strategies partially mediated the relationship between psychological capital and occupational well-being. Lastly, psychological capital significantly moderated the relationship between stress and occupational well-being positively. These results aid the organizations in choosing an approach to practice positive psychology, which in turn creates satisfied teachers with exceptional performance.